Characterization of grounds, pigments, binding media, and varnish coating of the Angel Michael' icon, 18th century, Egypt. (October 2016) - Sakr, Akmal A.; Ghaly, Mohamed F.; Geight, El-Sayed F.; Abdel-Haliem, Mahmoud E.F.
Abstract: Samples from canvas, grounds, pigments, and varnish coating from the icon of Angel Michael came back to the 18th century from the church of Samanod, Gharbeia Governorate, Egypt, were investigated using multispectral signals of SEM-EDX, FT-IR, and Mass spectrometry. The SEM data from the canvas indicated that it is of linen. EDX of the grounds indicated that they are of gypsum with natural impurities of halite, quartz, and clay minerals. FT-IR spectra of the grounds indicated that the binding medium was of animal glue where gypsum was mixed with animal glue. The SEM-EDX pattern of the orange pigment showed the presence of lead, minium (Pb3 O4 ) is the most probable, the blue color was Egyptian blue, whereas tetrahyrate [(Cu, Fe, Zn, Ag)12 Sb4 S18 )] may be used as a source of copper and crushed limestone was used as a source of flux. The gold color is composed red lead mixed with titanium oxide. The icon paintings were coated with a resinous layer of dammar, which had darkened into a brown color by photoxidation. Highlights: Animal glue was the most common grounds in icons. Red lead was used since the GreeK -Roman period. Red lead is transformed into black color of lead sulphide. Egyptian blue was the most common blue pigment in the Coptic period. Linen fibers of icons fibers are exposed to biodeterioration by microorganisms.